Trading dynamics with adverse selection and search: Market freeze, intervention and recovery - Jonathan Chiu; Thorsten V. Koeppl (Bank of Canada, 2011)
We study the trading dynamics in an asset market where the quality of assets is private information of the owner and finding a counterparty takes time. When trading of a financial asset ceases in equilibrium as a response to an adverse shock to asset quality, a large player can resurrect the market by buying up lemons which involves assuming financial losses. The equilibrium response to such a policy is intricate as it creates an announcement effect: a mere announcement of intervening at a later point in time can cause markets to function again. This effect leads to a gradual recovery in trading volume, with asset prices converging non-monotonically to their normal values. The optimal policy is to intervene immediately with minimal size when markets are deemed important and losses are small. As losses increase and the importance of the market declines, the optimal intervention is delayed and it can be desirable to rely more on the announcement effect by increasing the size of the intervention. Search frictions are important for all these results. They compound adverse selection, making a market more fragile with respect to a classic lemons problem. They dampen the announcement effect and cause the optimal policy to be more aggressive, leading to an earlier intervention at a larger scale.
Keywords: G1; E6; 330; Financial markets; Financial stability; Finanzmarkt; Wertpapierhandel; Informationswert; Ankündigungseffekt; Adverse Selektion; Theorie